Digital Media Literacy in the Training of Student Midwives (International Journal of Scientific Research and Management (IJSRM), 2022)
The optimization of the educational process in the higher medical school and the achievement of its basic goal - the formation of professional competencies of health professionals, requires the introduction of modern, interactive technologies and use of the advantages of digital and media technologies. The research aims to determine the role and importance of digital media literacy of midwife students for the process of acquiring professional competencies. An anonymous survey was conducted in the period December 2021 - January 2022, with 73 respondents, students majoring in midwifery, studying at the Faculty of Medicine and Haskovo Branch, Thrakia University, Stara Zagora, Republic of Bulgaria. The study identifies the following indicators of digital media literacy of students: frequency of use of the Internet and social media in educational activities, self-assessment of selection skills and effective use of information on health topics. It was ascertained: relatively good confidence of the midwife students in their own abilities to search and find adequate information, relevant to the set goals and objectives of the educational process; the need to further develop the digital media literacy of students in order to improve the effectiveness of educational activities.